From the Cuban revolution to the Cordobazo. Argentine Trotskyism against the armed struggle (1959-1969) - Mangiantini, Martín; Díaz, Javier (Cuadernos de Historia, 2023)
This article aims to investigate how political violence was conceptualized within the Argentine Trotskyist organizations of the 1960s. The influence of the Cuban Revolution, the growth of foquismo (theory of guerrilla warfare) and the crisis of the political regime impacted on their debates regarding the relation between violence and the development of a political strategy. We will analyze the positions towards armed struggle developed by the different organizations belonging to the field of Trotskyism concerning three aspects: the actions carried out, the controversies between various groups and the tensions and internal debates that led to crisis or splits from within and towards Trotskyism.